IMF Research Bulletin, December 2014. (IMF Research Bulletin; IMF Research Bulletin, 2014)
The December 2015 IMF Research Bulletin features a sampling of key research from the IMF. The Research Summaries in this issue look at 'The Impact of Deflation and Lowflation on Fiscal Aggregates (Nicolas End, Sampawende J.-A. Tapsoba, Gilbert Terrier, and Renaud Duplay); and 'Oil Exporters at the Crossroads: It Is High Time to Diversify' (Reda Cherif and Fuad Hasanov). Mahvash Saeed Qureshi provides an overview of the fifth Lindau Meeting in Economics in 'Meeting the Nobel Giants.' In the Q and A column on 'Seven Questions on Financial Frictions and the Sources of the Business Cycle, Marzie Taheri Sanjani looks at the driving forces of the business cycle and macroeconomic models. The top-viewed articles in 2014 from the IMF Economic Review are highlighted, along with recent IMF Working Papers, Staff Discussion Notes, and IMF publications.